2019
DOI: 10.1136/annrheumdis-2018-214200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt16 attenuates osteoarthritis progression through a PCP/JNK-mTORC1-PTHrP cascade

Abstract: ObjectivesWnt16 is implicated in bone fracture and bone mass accrual both in animals and humans. However, its functional roles and molecular mechanism in chondrocyte differentiation and osteoarthritis (OA) pathophysiology remain largely undefined. In this study, we analysed its mechanistic association and functional relationship in OA progression in chondrocyte lineage.MethodsThe role of Wnt16 during skeletal development was examined by Col2a1-Wnt16 transgenic mice and Wnt16fl/fl;Col2a1-Cre (Wnt16-cKO) mice. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 33 publications
(39 reference statements)
2
86
1
1
Order By: Relevance
“…17 Tong et al showed that Wnt16 overexpression protected cartilage in a model of osteoarthritis. 44 Wnt16 delayed cartilage breakdown by activating JNK and the WNT planar cell polarity pathway, thereby ultimately up-regulating PTHrP expression. 44…”
Section: The Case Of Wnt16mentioning
confidence: 99%
See 3 more Smart Citations
“…17 Tong et al showed that Wnt16 overexpression protected cartilage in a model of osteoarthritis. 44 Wnt16 delayed cartilage breakdown by activating JNK and the WNT planar cell polarity pathway, thereby ultimately up-regulating PTHrP expression. 44…”
Section: The Case Of Wnt16mentioning
confidence: 99%
“…Further complexity was added by the understanding that while a short burst of WNT activation supports articular cartilage formation and homeostasis, 17,57 excessively prolonged activation resulted in cartilage breakdown. Interestingly, WNT16 is both required and sufficient for cartilage homeostasis following cartilage injury, 17,44 and it is a partial activator of the canonical WNT pathway, maintaining "homeostatic levels" and preventing excessive activation from other more potent ligands. 17,44 The relevance of these findings to human osteoarthritis was confirmed by the association of allelic variants of WNT inhibitory molecules such as FRZB 74 and DOT1L 75 with osteoarthritis.…”
Section: Blockade Of Wnt Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Increasing evidence demonstrated that the articular cartilage and subchondral bone acted as a functional unit, and the interplay between them maintains the normal function of LFJ. 7,8 Subchondral bone provides structural support and shock absorber for superficial articular cartilage and undergoes dynamic balance between modeling and remodeling in response to mechanical stress. 9,10 The process of bone remodeling is regulated by osteoclast and osteoblast activity, and abnormal remodeling is believed to trigger the onset of OA.…”
mentioning
confidence: 99%